2020
DOI: 10.1057/s41260-020-00157-2
|View full text |Cite
|
Sign up to set email alerts
|

Piotroski’s FSCORE: international evidence

Abstract: Almost 20 years after its publication, Piotroski's (J Account Res 38:1-41, 2000) FSCORE, the composite measure of the firm's fundamental strength remains a strong predictor of subsequent stock returns and future profitability in international markets over the 2000-2018 period. Across developed non-US countries as well as emerging countries, high-FSCORE firms significantly outperform low-FSCORE firms by about 10% per year. Furthermore, FSCORE preserves its return-predictive power in all size segments after cont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 40 publications
1
8
0
2
Order By: Relevance
“…M-score model accurately identified the firms manipulating financial statements in Poland (Hołda, 2020). Likewise, many more studies have identified M-score model to be highly accurate in identifying companies falsifying financial statements (Omar et Piotroski's F-score is a composite accounting-based indicator of the corporation's fundamental strength and can be used to identify fundamentally weak firms (Walkshäusl, 2020). Regular F-score monitoring enables proactive risk management.…”
Section: Review Of Literature and Development Of Hypothesismentioning
confidence: 99%
“…M-score model accurately identified the firms manipulating financial statements in Poland (Hołda, 2020). Likewise, many more studies have identified M-score model to be highly accurate in identifying companies falsifying financial statements (Omar et Piotroski's F-score is a composite accounting-based indicator of the corporation's fundamental strength and can be used to identify fundamentally weak firms (Walkshäusl, 2020). Regular F-score monitoring enables proactive risk management.…”
Section: Review Of Literature and Development Of Hypothesismentioning
confidence: 99%
“…This can lead investors into the so‐called value trap, as value stocks may be cheap for a fundamentally justified reason 4 . That is why other contributions refine the B/P strategy by including additional metrics of fundamental performance or different proxies for intrinsic value—like Frankel and Lee (1998), Piotroski (2000), Bird and Gerlach (2003), Mohanram (2005), Piotroski and So (2012), Penman and Reggiani (2013, 2018), Lee (2015), Penman et al (2018), Asness et al (2019), Li and Mohanram (2019), Walkshäusl (2020) and Huefner et al (2021). These studies provide evidence for the predictive ability of fundamental quality for future stock returns on the US market before and after the financial crisis.…”
Section: Combining Research On Valuation Accuracy Valuation Bias and ...mentioning
confidence: 99%
“…Motivated by recent strong evidence for the FSCORE criterion on a stand-alone basis (e.g., see Choi and Sias 2012;Duong et al 2014;Ng and Shen 2020;Walkshäusl 2020), it might also be worthwhile for future studies to revise the research design so that the FSCORE is the primary criterion, being possibly supplemented by other selection criteria. In addition, the methods employed in this paper could be applied to other stock markets to uncover the extent to which our results based on the German sample data are generalizable.…”
Section: Conclusion and Implications For Further Researchmentioning
confidence: 99%
“…This results in relatively narrow portfolios during the holding periods following such portfolioreformation points, at which the total number of high-FSCORE stocks in the tertile portfolio formed on the primary criterion was low. In accordance with recent studies on the FSCORE (e.g., see Choi and Sias 2012;Piotroski and So 2012;Zhu et al 2019;Ng and Shen 2020;Walkshäusl 2020), we extend the group of high-FSCORE stocks to also include stocks with an FSCORE of 7 to keep the FSCORE-related portfolios sufficiently diversified throughout the sample period. This extension is particularly important because raising the market-cap threshold outstandingly narrows the sample.…”
Section: Introductionmentioning
confidence: 95%